2015
DOI: 10.12816/0024682
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge , Attitudes and Practice of Restoring Endodontically Treated Teeth by Dentists in North of Saudi Arabia

Abstract: Abstract:Objectives: The aim of this study was to determine the knowledge, current approaches, techniques and practices for the restoration of endodontically treated teeth (ETT) among general dental practitioners and specialists in north of Saudi Arabia. Methodology:A standard questionnaire based survey containing 16 multiple choice questions about techniques and treatment methods, frequency of post, type of post, choice of luting cement, core material, reason of failure of endodontic treatment was distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…ferrule. 35 The importance of ferrule can never be neglected as it not only increases the fracture resistance of the tooth but also act as foundation for restoration. In a research, it was found that 72% of the participants believe that in endodontically treated teeth (ETT) ferrule effect is a major factor that causes a fracture resistance, while 54% conclude that tooth tissue preservative and post reinforces declines the chances of a fracture.…”
Section: Discussionmentioning
confidence: 99%
“…ferrule. 35 The importance of ferrule can never be neglected as it not only increases the fracture resistance of the tooth but also act as foundation for restoration. In a research, it was found that 72% of the participants believe that in endodontically treated teeth (ETT) ferrule effect is a major factor that causes a fracture resistance, while 54% conclude that tooth tissue preservative and post reinforces declines the chances of a fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained among Saudi Arabia dentists. Akbar et al (22) showed that prosthodontists use metal post (11.7%) more often than fiber post (5.2%), which is opposite for general practitioners, who use fiber posts (35.9%) more often than metal posts (31.3%). Kavleker et al (23) reported that both, prosthodontists and general practitioners use fiber post more often than metal posts.…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabian dentists reported similar mistakes. Crown fracture (45%) is the most common reason for failure, followed by endodontic failure (31%) and root fracture (18%) (22) .…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was prepared based on previous similar studies and it was modified according to scenario of Nepal. [14][15][16][17][18][19][20]23 Convenience sampling method was selected in this study. For collection of data a Google form was created with the questionnaire along with a consent section and the message containing link to it was sent to 114 Prosthodontists through electronic communication media (Viber, Messenger and Whatsapp).…”
Section: Methodsmentioning
confidence: 99%
“…There have been several studies among various dental professionals on their knowledge, attitude and clinical practice on post and core therapy on endodontically treated tooth in the past and these studies can give us some insight about the status of post and core therapy on those countries and regions. [14][15][16][17][18][19][20][21][22][23] This present study aims towards finding out the scenario of treatment of endodontically treated tooth with post and core by Prosthodontists of Nepal.…”
Section: Introductionmentioning
confidence: 99%